If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 6 = x + 60 Reorder the terms: 6 + 7x = x + 60 Reorder the terms: 6 + 7x = 60 + x Solving 6 + 7x = 60 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 6 + 7x + -1x = 60 + x + -1x Combine like terms: 7x + -1x = 6x 6 + 6x = 60 + x + -1x Combine like terms: x + -1x = 0 6 + 6x = 60 + 0 6 + 6x = 60 Add '-6' to each side of the equation. 6 + -6 + 6x = 60 + -6 Combine like terms: 6 + -6 = 0 0 + 6x = 60 + -6 6x = 60 + -6 Combine like terms: 60 + -6 = 54 6x = 54 Divide each side by '6'. x = 9 Simplifying x = 9
| 4(7-n)-(1-8n)=8n | | 12-3x+2x=-3 | | 0.17y+0.09(y+8000)=2540 | | 7x-9=-9+7x | | 0=4x^2-16x-16-2x-4-2 | | 2x+10=x+19 | | 0.3(22)^1/2 | | 15-6x+7x=-25+5x | | 6c+4-c=25 | | 4x+5=5+2x+18 | | M+6.4=9 | | 3(5x+-3)=5(x+-1) | | 3.8x+-13=1.4x+5 | | 4x+7=2(2x+1) | | 2(-3+y)+2y=2 | | 5y+3(-8)=3(y+2)-3 | | 2(18+L)+2L=96 | | -2(6x+9)+1= | | 8-y= | | 8-y=3x-12 | | 8+7x=3x+16 | | T^2=-144 | | 2+5x+4x=11 | | 39=3x+3x+3 | | 6+7x+5x=54 | | 8+2x+4x=74 | | 5-6.5x=-29.25 | | 6[-3+7(-8+6)]= | | 8+2x+rx=74 | | 58=x+4x+8 | | (2a/1049)-(a/1049)=1049 | | 3/15+1/20 |